2023
DOI: 10.3390/molecules28031413
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Supplements Affecting Producer Microorganisms in Food Biotechnology: A Review

Abstract: Microorganisms, fermentation processes, and the resultant metabolic products are a key driving force in biotechnology and, in particular, in food biotechnology. The quantity and/or quality of final manufactured food products are directly related to the efficiency of the metabolic processes of producer microorganisms. Food BioTech companies are naturally interested in increasing the productivity of their biotechnological production lines. This could be achieved via either indirect or direct influence on the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 201 publications
0
3
0
Order By: Relevance
“…(2022a) and Dysin et al . (2023) who found that soy protein hydrolysate serves as an exogenous nitrogen source, providing free amino acids, low‐molecular‐weight peptides and growth factors that contribute to the stimulation of lactic acid bacteria growth. The promotion effect of zinc on the growth of LB was also similar to the finding of Karami (2018) that moderate amounts of trace elements can promote the growth of LAB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022a) and Dysin et al . (2023) who found that soy protein hydrolysate serves as an exogenous nitrogen source, providing free amino acids, low‐molecular‐weight peptides and growth factors that contribute to the stimulation of lactic acid bacteria growth. The promotion effect of zinc on the growth of LB was also similar to the finding of Karami (2018) that moderate amounts of trace elements can promote the growth of LAB.…”
Section: Resultsmentioning
confidence: 99%
“…Fermented milk, with its unique texture, flavour and health benefits, becomes increasingly popular worldwide. The active LAB, one of the most important probiotics, in fermented milk has been widely used in the food fermentation industry because it can not only enhance the texture and flavour of fermented milk but also maintain the balance of intestinal flora and boost human immunity (Wang et al ., 2021, Rothstein et al ., 2020, Dysin et al ., 2023). Probiotic foods must have a minimum of 10 6 cfu/g of probiotics to be sold.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary administration of probiotics can enhance the body's natural immune function. The bacteria may adhere transiently to the gastrointestinal tract and colonize it, increasing antibody production (Dysin et al, 2023). Probiotics have been shown to improve disease resistance and animal growth in animal rearing.…”
Section: Immune System Responsementioning
confidence: 99%
“…They are natural or identical to them. Also included in this category are probiotic microorganisms [2]. Biologically active supplements are not medicines, but food products that enrich the human diet [3].…”
Section: Introductionmentioning
confidence: 99%